Scattering of plane waves by the junction of transmissive and soft-hard half-planes - Büyükaksoy, A; Çinar, G; Serbest, AH (Springer International Publishing Ag, 2004)
A uniform asymptotic high frequency solution is developed for the diffraction of plane waves by the junction of two half-planes. One of the half-planes is assumed to be characterized by Senior's resistive-type partially transmissive boundary conditions and the other is soft at the top and hard at the bottom. The related boundary-value problem is formulated as a matrix Wiener-Hopf equation which is solved explicitly through the Daniele-Khrapkov method. Some graphical results are also presented.
Keywords: diffraction; Wiener-Hopf theory; matrix factorization